Evaluation of Advanced Bionics high resolution mode. - Buechner A; Frohne-Buechner C; Gaertner L; Lesinski-Schiedat A; Battmer R; Lenarz T (International Journal of Audiology, 2006)
The objective of this paper is to evaluate the advantages of the Advanced Bionic high resolution mode for speech perception, through a retrospective analysis. Forty-five adult subjects were selected who had a minimum experience of three months' standard mode (mean of 10 months) before switching to high resolution mode. Speech perception was tested in standard mode immediately before fitting with high resolution mode, and again after a maximum of six months high resolution mode usage (mean of two months). A significant improvement was found, between 11 and 17%, depending on the test material. The standard mode preference does not give any indication about the improvement when switching to high resolution. Users who are converted within any study achieve a higher performance improvement than those converted in the clinical routine. This analysis proves the significant benefits of high resolution mode for users, and also indicates the need for guidelines for individual optimization of parameter settings in a high resolution mode program.